Intelligent wearable interfaces - Xu, Yangsheng (Wiley-Interscience, 2008)
Intelligent Wearable Interfaces is a collection of the efforts the authors have made in this area at The Chinese University of Hong Kong. They introduce methodologies to develop a variety of intelligent wearable interfaces and cover practical implementations of systems for real-life applications. A number of novel intelligent wearable interface systems are examined, including: Network architecture for wearable robots, Wearable interface for automatic language translation, Intelligent cap interface for wheelchair control , Intelligent shoes for human-computer interface , Fingertip human-computer interface , Ubiquitous 3D digital writing instrument , Intelligent mobile human airbag system